Efek pH Terhadap Pelepasan Fosfat Oleh Lumpur Aktif Dalam Kondisi Anaerob - Jubhar Christian Mangimbulude (Universitas Atma Jaya Yogyakarta, 2003)
Phosphate removal in domestic wastewater or industrial wastewater is a key factor of prevent eutrophication. Mechanisms of biological phosphate removal occurs under both of anaerobic and aerobic conditions. Phosphate up take under aerobic condition is much determined by phosphate released under anaerobic condition. The objective of this research was to understand the effect of various of external pH on phosphate released by activated sludge under anaerobic conditions. For that purpose, the experiments were conducted in batch system under anaerobic condition at pH of 6.0, 7.0, 8.0 and 9.0 separetely. PO4, Acetate and MLVSS were measured and used as parameters to analyze process. The results shown that the highest of phosphate released and acetate consumed occurred at pH 9.0 and the lowest it was occurred at pH 6.0. The value of phosphate/acetate ratio was calculated to be in variation of 0.161 to 0.256 p-mol/C-mol in pH range of 6.0 to 9.0